The impact of the COVID-19 pandemic on maternal healthcare costs: a time series analysis of pregnancies of multi-ethnic mothers in South London, United Kingdom - Alice McGreevy; Marina Soley-Bori; Florence Tydeman; Kathryn V. Dalrymple; Sara L. White; Asma Khalil; Lucilla Poston; Emma L. Duncan; Tisha Dasgupta; Hiten D. Mistry; Julia Fox-Rushby; Peter von Dadelszen; et al. (BMC Medicine)
Abstract Background Due to the COVID-19 pandemic, maternity care reconfigurations disrupted in-person care, which shifted towards virtual care and self-monitoring. We assessed the impact of these changes on maternity service provision costs. Methods Data from October 2018 to April 2023 were used from the population-based early-LIfe data cross-LInkage in Research, Born in South London (eLIXIR-BiSL) platform linking maternity, neonatal, and mental healthcare data from three National Health Service (NHS) hospitals in South London, United Kingdom. Maternity costs were generated from the NHS perspective, using national unit costs and individual-level use of maternity, mental health, and primary care services. Interrupted time series analysis estimated the pandemic impact on monthly mother-newborn costs over time. Cross-sectional pre-pregnancy cost models isolated the impact of virtual care and gestational diabetes (GDM) self-monitoring using the GDm-Health app. Ethnic inequalities in the impact of the pandemic on maternity costs were assessed via interaction terms. Results Among 36,895 pregnancies, the monthly cost time series level dropped by 4% (£ − 38, 95% confidence interval: [£ − 65 to − 10]), during the first pandemic lockdown, and by 7.6% (£ − 72 [£ − 108 to − 36]), when lockdowns were lifted compared with the pre-pandemic period. However, the pre-pandemic slightly upward timeseries slope of costs (£4 per month, [£0.30 to £6.83]) was unchanged during the pandemic (£0.46 [£ − 2.93 to 3.84]). Monthly costs increased with first lockdown for Black (£103 [£26 to 181]) and Asian women (£128 [£38 to 218]) and increased more slowly during post-lockdown (£ − 12 [£ − 23 to − 2]), for Asian women, remaining higher throughout the pandemic for Black and Asian women compared with White women. A 1% increase in virtual care was associated with a £7 (£3 to 10) increase in maternity costs. GDM self-monitoring via GDm-Health was cost-neutral (£140 [£ − 68 to 348]). Conclusions The pandemic was associated with temporary reductions in maternity costs due to lower healthcare utilisation. Ongoing, rising maternity costs were unchanged. The pandemic had differential effects on Black and Asian women compared with White women. Further research is needed into clinical outcomes of virtual care (associated with higher costs) and use of GDm-Health (cost-neutral).